Pengaruh NPF, BOPO, DPK terhadap Profitabilitas pada Perbankan Syariah Indonesia Tahun 2019-2022 - Alia Damaiyanti; Selly Puspitasari; Fauzan Fuadi (Journal on Education, 2024)
This research objective was to test and analyze the influence of Non-Performing Financing (NPF), Operating Expense Operating Income (BOPO), and Third Party Funds (DPK) on profitability in sharia banking in 2019-2022. The method used is quantitative research and the sampling technique used in this research is purposive sampling, where the population in this study consists of 64 banking data. Based on the sample criteria, the total research sample was 48 banking data. The data type in this research is secondary data which was tested using SPSS version 25 with multiple linear regression analysis techniques. The research results show that NPF (X1) has no partial effect on profitability, BOPO (X2) has partial effect on profitability, DPK (X3) has a partial effect on profitability. It showed that NPF, BOPO , DPK have an effect on profitability simultaneously.